STRATEGI PUBLIC RELATIONS MELALUI PROGRAM CSR DALAM MENINGKATKAN CITRA POSITIF PADA PT TransJakarta - Inas Vhatinah; Iin Soraya (Jurnal Sarjana Ilmu Komunikasi (J-SIKOM), 2026)
Jakarta's growing urban mobility challenges PT TransJakarta to build public trust amidst persistent safety and service quality issues. This study aims to analyze PT TransJakarta's Public Relations strategy in designing and implementing Corporate Social Responsibility (CSR) programs as an effort to build a positive corporate image. The research employs a qualitative approach with a case study design, involving two internal informants, namely the Head of Public Relations & CSR Department and the CSR Coordinator, selected through purposive sampling. Data were collected through in-depth interviews, observation, documentation, and literature review, subsequently analyzed using Miles and Huberman's interactive model. The findings reveal that PT TransJakarta's CSR communication is predominantly characterized by the Press Agentry Model and Public Information Model, reflected through massive digital platform publications and sustainability reports. The Two-Way Asymmetrical and Two-Way Symmetrical Models have only been partially implemented through strategic partnerships. This research contributes academically by enriching PR communication strategy studies within the public transportation sector of state-owned regional enterprises. It is recommended that PT TransJakarta develop a more inclusive participatory dialogical approach grounded in the community's actual needs. Keywords: Communication Strategy, Corporate Image, Corporate Social Responsibility, Public Relations, Public Transportation